(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The bodys defenses are determined by systemic and local factors. Local protection is provided by the integrity of the oral mucosa, the microbicidal properties of saliva and lymphoid tissue. The integrity of the oral mucosa is the best physiological barrier to infection. Protective factors of saliva are determined not only by its mechanical properties, but also depend on the biological substances dissolved in it, which can cause the lysis of foreign agents. These substances include lysozyme, immunoglobulin A, and a large number of interleukins that have a bactericidal and antiviral effect. A powerful factor of local protection is the secretory IgA contained in saliva.